Solve for y 4y-8=6y-3

Math
4y-8=6y-3
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 6y from both sides of the equation.
4y-8-6y=-3
Subtract 6y from 4y.
-2y-8=-3
-2y-8=-3
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 8 to both sides of the equation.
-2y=-3+8
Add -3 and 8.
-2y=5
-2y=5
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2y=5 by -2.
-2y-2=5-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2y-2=5-2
Divide y by 1.
y=5-2
y=5-2
Move the negative in front of the fraction.
y=-52
y=-52
The result can be shown in multiple forms.
Exact Form:
y=-52
Decimal Form:
y=-2.5
Mixed Number Form:
y=-212
Solve for y 4y-8=6y-3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top